2016
DOI: 10.1007/s13277-016-5315-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CD26 inhibits growth and metastasis of pancreatic cancer

Abstract: CD26/DPPIV is a glycosylated transmembrane type II protein and has a multitude of biological functions, while its impact on the malignant phenotypes of cancer cells has not been fully understood. This study aimed to investigate the effect of CD26 on growth and metastasis of pancreatic cancer cells in vitro and in vivo. We found in this study that CD26 expression was higher in cell lines that derived from the metastatic sites than those from the primary tumor sites. In specimens of pancreatic cancer patients, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…Despite previous reports that DPP4 knockdown reduces human PDAC cell line proliferation in vitro, 26 we found that BXCL701 had no effect on mT3-2D proliferation or viability in vitro (online supplemental figure 1B-D). To test BXCL701's impact on PDAC tumor growth in vivo, we injected C57BL/6 mice subcutaneously with 1×10 5 mT3-2D cells, waited for the tumors to reach 40-50 mm 3 , then began BXCL701 treatment.…”
Section: Dpp Inhibitor Bxcl701 Reduces Mt3-2d Tumor Growth and Prolongs Overall Survivalcontrasting
confidence: 99%
“…Despite previous reports that DPP4 knockdown reduces human PDAC cell line proliferation in vitro, 26 we found that BXCL701 had no effect on mT3-2D proliferation or viability in vitro (online supplemental figure 1B-D). To test BXCL701's impact on PDAC tumor growth in vivo, we injected C57BL/6 mice subcutaneously with 1×10 5 mT3-2D cells, waited for the tumors to reach 40-50 mm 3 , then began BXCL701 treatment.…”
Section: Dpp Inhibitor Bxcl701 Reduces Mt3-2d Tumor Growth and Prolongs Overall Survivalcontrasting
confidence: 99%
“…Our results indicated that CD26 was aberrantly expressed in pancreatic tumors and may be involved in pancreatic tumorigenesis as an oncogene, which corroborates the findings of our previous study. 9 Similarly to our results, CD26 was overexpressed in patients with thyroid cancer, 7 , 14 malignant mesothelioma, 15 ovarian carcinoma, 16 and HCC. 17 Particularly, in patients with HCC, CD26 overexpression was correlated with the proliferation marker ki-67 in tumor cells, thereby indicating that CD26 expression may be involved in tumorigenic proliferation.…”
Section: Discussionsupporting
confidence: 88%
“… 8 Our previous work showed that CD26 overexpression promotes the growth and invasion of pancreatic cancer cells, whereas suppression of CD26 inhibits malignant behaviors. 9 However, CD26 expression in specimens from patients with pancreatic tumors has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that suppression of CD26 expression inhibited metastasis of pancreatic cancer 29 . Moreover, the flavonoid apigenin restrained metastasis of lung cancer by downregulation of CD26 30 .…”
Section: Introductionmentioning
confidence: 96%